A Dialogue on Explanation - Mantzavinos, C. (SpringerBriefs in Philosophy,, 2018)
This book introduces a panorama of the philosophical theory of explanation. The author writes it as a philosophical dialogue between two interlocutors, Philip and a student. In the process of their talk, the two present a defense of the position of explanatory pluralism. The fictional dialogue takes place on Cape Sounion, near Athens where the two interlocutors enjoy the view over the Aegean Sea. An initial exchange of arguments leads to a dialogue that unfolds the panorama of the contemporary philosophical theory of explanation. The second part of the dialogue details an exchange of arguments on explanatory pluralism as a novel approach to the philosophical theory of explanation. The two also discuss historical cases as well as the ways in which explanatory progress in science can be attained. We are all philosophers and we develop our own philosophy by exchanging views and arguments. The dialogue form is and should remain the principal form of philosophizing, since ideas, like butterflies, do not merely exist - they develop. This is certainly the case in actual philosophical interaction. As this book aptly demonstrates, it can also be the case in written philosophical exposition. The engaging dialogue captured here will help readers to better understand the philosophical theory of explanation.